RESILIENCE OF RURAL COCONUT FARMERS IN TANJUNG RAJA VILLAGE, KATEMAN DISTRICT, INDRAGIRI HILIR REGENCY SOUTH SUMATRA, INDONESIA - Irwan, Irwan; Mariyana, Mariyana; Mobo, Froilan D; Saragih, Sepriandison; Andri Siahaan, Kevin William; Lestari, Fitria (Journal of Agriculture and Technology Management; Vol 26 No 1 (2023): Vol 26 No 1 (2023): Journal of Agriculture and Technology Management (JATM) Volume 26 January - June 2023 Issue, 2023)
This study aims to analyze the livelihoods of coconut farmers in Tanjung Raja Village and describe the factors that affect farmers' livelihoods in Tanjung Raja Village, Indragiri Hilir Regency, South Sumatra. Sampling was carried out descriptively with data collection methods using interviews, document data collection, and observation collection methods, and data analysis using the Miles and Hubermen model. The results showed that most of the population in Tanjung Raja Village are coconut farmers, and some of them are coconut farmers who do not own their own land. Thus, the factor that most influences the existence of coconut farm workers in Tanjung Raja Village is the limited expertise of the population who have only graduated from elementary school, as many as about 30 people, or around 68.1% of them, making it difficult for them to work in other fields. First, the livelihood on the small island of Tanjung Raja Village only comes from coconut plantations. Second, farm laborers do not have skills and abilities in other fields, and third, they have a low level of education.